2001
DOI: 10.1139/f01-102
|View full text |Cite
|
Sign up to set email alerts
|

Primary determinants of macrophyte community structure in 62 marshes across the Great Lakes basin: latitude, land use, and water quality effects

Abstract: We collected water quality, land use, and aquatic macrophyte information from 62 coastal and inland wetlands in the Great Lakes basin and found that species richness and community structure of macrophytes were a function of geographic location and water quality. For inland wetlands, the primary source of water quality degradation was inputs of nutrients and sediment associated with altered land use, whereas for coastal wetlands, water quality was also influenced by exposure and mixing with the respective Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
3
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 25 publications
3
62
3
1
Order By: Relevance
“…Shallow water systems are at great risk of being impacted by a variety of environmental stressors owing to their location in watersheds . Longterm changes in macrophyte communities have indeed been documented throughout the world (Brush andHilgartner 2000, Sand-Jensen et al 2000) and have been associated most often with changes in water quality (Sand-Jensen et al 2000, Lougheed et al 2001 and changes in hydrology (Keddy and Reznicek 1986). The current study decreased water level of the mesocosms to the point that aboveground structures desiccated.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Shallow water systems are at great risk of being impacted by a variety of environmental stressors owing to their location in watersheds . Longterm changes in macrophyte communities have indeed been documented throughout the world (Brush andHilgartner 2000, Sand-Jensen et al 2000) and have been associated most often with changes in water quality (Sand-Jensen et al 2000, Lougheed et al 2001 and changes in hydrology (Keddy and Reznicek 1986). The current study decreased water level of the mesocosms to the point that aboveground structures desiccated.…”
Section: Discussionsupporting
confidence: 47%
“…Indeed, Barrat-Segretain (2001) showed that reestablishment of submersed aquatic plants after a disturbance either occurred through resprouting of underground plant parts or by vegetative fragments, each strategy related to high below-or aboveground biomass, respectively. Species-specific responses to environmental stress and simultaneous effects on ecosystem processes are poorly understood for freshwater submersed aquatic plants, even though this group of species shows strong responses to changes in the environment (Roelofs 1983, Lougheed et al 2001) and is recognized for its important effects on ecosystem processes (Carpenter and Lodge 1986). Here, I show that four common submersed aquatic macrophyte species differ in their effects on ecosystem properties and their response to environmental stress (temporary water draw-down).…”
Section: Discussionmentioning
confidence: 87%
“…3; r 2 ϭ 0.32, P Ͻ 0.0001), leveling off at ϳ10 species of submergent plants and a WZI value of 4. This is not unexpected, given the significant relationship between submergent plants species richness and wetland water quality (Crosbie and Chow-Fraser 1999;Lougheed et al 2001).…”
Section: Development Of Wetland Zooplankton Index (Wzi)mentioning
confidence: 85%
“…Second, zooplankton taxa often have different preferences for trophic state Bertilsson 1989, Berzins andPejler 1989) , and therefore species replacement will also occur with water quality degradation. Finally, since the species richness of submersed macrophytes declines as marshes become eutrophic and degraded (Crosbie and Chow-Fraser 1999;Lougheed et al 2001), we hypothesize that the zooplankton community should reflect changes in the plant community as we proceed along the trophic-degradation gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Another technique used in the literature is to use simple univariate regressions of land use on water quality (see, e.g. Lougheed, 2001). Limiting the model to one period, or not controlling for other factors that can affect water quality can potentially bias the coefficients of interest.…”
Section: Introductionmentioning
confidence: 99%